Establishment of Axenic Culture and Induction of Somatic Embryogenesis in Kapur Bukit (Dryobalanops beccarii Dyer) - Norshahidah, Osman (Universiti Malaysia Sarawak, UNIMAS, 2010)
Kapur Bukit (Dryobalanops beccarii Dyer) a medium hardwood in Dipterocarpaceae has been identified as one of the timber species recommended for forest plantation in Sarawak. Establishment of forest plantation requires mass quantity of the planting stocks. Since clonal propagation of this species by the conventional methods is difficult and slow, micropropagation using the in vitro culture technique has been considered as an alternative method to mass produce clonal material for planting. Micropropagation using field-derived stock plant required effective measures to establish contamination-free and viable culture and successful regeneration of plant regeneration in vitro. The first objective of this project is to establish axenic and viable explants in culture. The second objective is to induce somatic embryogenesis. Results of this study showed that immersing in 0.3% Benomyl (w/v) for one hour after surface sterilization could reduce fungal contamination to certain extent. Browning problem that lead to death of explant can be overcome by trimming explants in acid solution and incorporating of PVP, citric acid and ascorbic acid in WPM medium. It was found root developed from compact and friable callus induced by 2, 4-D. To date, no somatic embryogenesis was observed.